Cauda equina syndrome following an uneventful spinal anesthesia in a patient undergoing drainage of the Bartholin abscess: A case report. Issue 19 (May 2018) - Merino-Urrutia, Waldo; Villagrán-Schmidt, Milca; Ulloa-Vásquez, Priscilla; Carrasco-Moyano, Rubén; Uribe, Alberto; Stoicea, Nicoleta; Bergese, Sergio D.
Abstract: Rationale: Neuraxial anesthesia is a commonly used type of regional anesthesia. Cauda equina syndrome is an unusual and severe complication of neuraxial anesthesia, and is caused by damage to the sacral roots of the neural canal. We present a case of cauda equina syndrome following spinal anesthesia in a patient who underwent Bartholin abscess drainage. Patient concerns: A 23-year old female scheduled to undergo surgical drainage of Bartholin abscess. Spinal anesthesia was performed with bupivacaine and fentanyl. There were no perioperative adverse events reported. On postoperative day 1, the patient went to the emergency department describing bilateral weakness and pain of the lower extremities (LE). Diagnoses: Lumbar magnetic resonance imaging showed increased gadolinium accumulation in the neural sheath at the level of the cauda equina tracts, consistent with the diagnosis of arachnoiditis and the diagnosis of cauda equina was established. Interventions: The patient received the following emergent treatment: 75 mg pregabalin (oral) every 12 hours, 20 mg (8 drops) tramadol (oral) every 8 hours, and 4 mg dexamethasone (intravenous) every 6 hours. On postoperative day 4, the patient still experienced bilateral flaccid paraparesis (accentuated in the left side), neuropathic pain in low extremities, and left brachial monoparesis. Hence, dexamethasone was instantly replaced with 1 g methylprednisolone (intravenous) for 5 days. Outcomes: After completing 5 days of methylprednisolone, on postoperative day 9, the patient experienced less pain in left extremities, osteotendinous reflexes were slightly diminished, and she was able to walk with difficulty for 3 to 5 minutes. Greater mobility was evidenced, with right proximal and distal low extremities Medical Research Council Scale grades of 2 and 3 and left proximal and distal low extremities Medical Research Council Scale grades 1 and 2, respectively. Oral prednisone was restarted. Consequently, she was discharged home in stable conditions on postoperative day 25 with a prescription for sertraline, clonazepam, pregabalin, paracetamol, and prednisone. Lesson: The early detection and treatment of complications after neuraxial anesthesia is essential to minimize the risk of permanent damage.